4
$\begingroup$

We are given a function $h(x)$ which strictly positive. The function $h$ is defined on $\mathbb{R}$ and that satisfies the following:\

$$\lim_{x\to 0}(h(x)+\frac{1}{h(x)})=2$$

The question is to prove that the limit of $h$ exists at$ 0$ and then find its limit as $x\to 0$

If we assume that the limit exists (say it's equal to $\lambda$, then we have $\lambda+\frac{1}{\lambda}=2$ and by solving this equation, we get $\lambda=1$. However, I am completely clueless on how to prove the existence of the limit of $h(x)$ when $x\to 0$.

$\endgroup$
1
$\begingroup$

Let $g(x)=\sqrt{h(x)}$. We have $$h(x)-\frac{1}{h(x)}-2=\left(g(x)-\frac{1}{g(x)}\right)^2.$$

This has limit $0$, so $g(x)-\frac{1}{g(x)}$ has limit $0$. We show that $g(x)$ has limit $1$. Note that $|g(x)|$ is bounded above, so $g^2(x)-1$ has limit $0$. Since $g(x)+1\gt 1$, it follows that $g(x)-1$ has limit $0$.

$\endgroup$
2
$\begingroup$

We have $h(x) +\dfrac 1{h(x)} \to 2$, so $$f(x) :=h(x) +\dfrac 1{h(x)}-2=\frac{h(x)^2 -2h(x) + 1}{h(x)}=\frac{(h(x) - 1)^2}{h(x)}\to 0$$as $x \to 0$.

Show that for $x$ sufficiently small $h(x)$, we have $\frac12<h(x) < 2$ (any upper bound will work). So $$f(x)>\frac12\big(h(x)-1\big)^2$$

Now can you use the squeeze theorem to derive the result?

$\endgroup$
  • 1
    $\begingroup$ Since $(h - 1)^{2}/h \to 0$ and $h$ is bounded we can say that $(h - 1)^{2} \to 0$ and then $h \to 1$. $\endgroup$ – Paramanand Singh Sep 9 '14 at 6:32
2
$\begingroup$

Suppose there is a sequence $(x_n)$ such that $x_n \to 0$ but $h(x_n) \to 1$ is not true.

Then there is a $\delta > 0$ such that either,

a) $ h(x_n) > 1 + \delta$ for infinitely many values of $n$,or,

b) $0 < h(x_n) < \dfrac{1}{1+\delta}$ for infinitely many values of n.

If b) holds assume (by choosing a subsequence if necessary) that $ 0 < h(x_n) < \dfrac{1}{1+\delta}$ for all $n$.

The boundedness of $h(x_n)$ implies we can find a subsequence $(y_n)$ of $(x_n)$ such that $\lim h(y_n) = L$ exists and $ 0 \leq L \leq \dfrac{1}{1+\delta} < 1 $.

$L \neq 0 $ as a 0 limit will contradict $h(y_n) + \dfrac{1}{h(y_n)} \to 2 $ a consequence of the given condition.

But this implies $\dfrac{1}{h(y_n)}$ also converges to $\dfrac{1}{L}$ with $L + \dfrac{1}{L} = 2$ and $L = 1$, a contradiction to $ L < 1$.

If $h(x_n) > 1 + \delta$ infinitely often, then $ 0 < \dfrac{1}{h(x_n)} < 1/(1+\delta)$ infinitely often, and the argument proceeds similarly to obtain a contradiction.

Hence, for any $x_n \to 0$ $h(x_n) \to 1$, hence $\lim h(x) = 1$ as $x \to 0.$

$\endgroup$
1
$\begingroup$

Let $g(x) = x + x^{-1}$. Then your limit is

$$ \lim_{x \to 0} g(h(x)) = 2 $$

$g$ isn't quite an invertible function: for every point $a \in (2, \infty)$ there are two solutions to $g(x) = a$. But in some sense it's a continuous two-valued 'function': if I let $f^+$ and $f_-$ be the larger and smaller of the two solutions, then they are both continuous functions:

$$ \lim_{x \to 0} f_+(g(h(x))) = f_+(2) = 1 $$ $$ \lim_{x \to 0} f_-(g(h(x))) = f_-(2) = 1 $$

So in some sense, we whould be able to say

$$ \lim_{x \to 0} g^{-1}(g(h(x)) = g^{-1}(2) = \{1\} $$ $$ \lim_{x \to 0} \{ h(x), h(x)^{-1} \} = \{1\} $$

and since we just get one limit point, the individual limits should exist (i.e. $h(x) \to 1$). All that's left is finding a way to make a precisely statement that captures this idea, and then prove the theorem saying we can find limits like this. This is a fair bit of work, but a good idea in the long run since it gives us a new tool useful for dealing with more problems!

$\endgroup$
  • $\begingroup$ I'm not sure I understand. We haven't assumed anything about the continuity of $f$ here $\endgroup$ – Mathmo123 Sep 9 '14 at 12:24
-1
$\begingroup$

Note that if either $h(x)$ or $\frac{1}{h(x)}$ is not bounded in $(-\varepsilon, \varepsilon)$ then the original limit cannot exist. We'll use that property further, refering it as $(*)$

$$\lim_{x\to 0}\left(h(x) + \frac{1}{h(x)}\right) = 2 \Leftrightarrow \lim_{x\to 0}\left(h(x) -2 + \frac{1}{h(x)}\right) = 0 \Leftrightarrow \lim_{x\to 0}\left(\sqrt{h(x)} - \frac{1}{\sqrt{h(x)}}\right)^2 = 0 \Leftrightarrow \lim_{x\to 0}\left(\frac{h(x) - 1}{\sqrt{h(x)}}\right)^2 = 0 \Leftrightarrow \lim_{x\to 0}\frac{(h(x) - 1)^2}{h(x)} = 0 \stackrel{(*)}{\Rightarrow} \lim_{x\to 0}(h(x)-1)^2 = 0$$

Wich means that $$\lim_{x\to 0} h(x) = 1$$

$\endgroup$
  • $\begingroup$ The last $\iff$ requires that you know that both the numerator and denominator have limits. But that the denominator has limit is what you're trying to prove! $\endgroup$ – Kim Jong Un Sep 9 '14 at 2:09
  • $\begingroup$ You are saying that $\lim\frac fg = \frac{\lim f}{\lim g}$. Why doesn't this assume the convergence of $f$ and $g$? $\endgroup$ – Mathmo123 Sep 9 '14 at 2:10
  • $\begingroup$ If $h(x) \to \pm\infty$ as $x \to 0$ then $\lim \left( h(x) + \frac{1}{h(x)} \right)$ does not exist. This says nothing about other kinds of divergence. $\endgroup$ – user164587 Sep 9 '14 at 2:22
  • $\begingroup$ @user164587 But that very limit exists by hypothesis of the problem. $\endgroup$ – Darth Geek Sep 9 '14 at 2:23
  • 1
    $\begingroup$ That's my point! $h(x)$ is bounded. $\endgroup$ – user164587 Sep 9 '14 at 2:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.